GAMBARAN FAKTOR YANG TERKAIT DENGAN PENEMUAN KASUS TUBERKULOSIS PARU DI KABUPATEN BATANG BERDASARKAN KARAKTERISTIK, KINERJA PETUGAS DAN FASILITAS LABORATORIUM PUSKESMAS - Meza Nuraisya; Mateus Sakundarno Adi; Lintang Dian Saraswati (Jurnal Kesehatan Masyarakat (Undip), 2018)
Tuberculosis is an infectious disease caused by mycobacterium tuberculosis. Case finding of tuberculosis is one of the main strategies for tuberculosis control. Case Detection Rate (CDR) and Case Notification Rate (CNR) of Batang Regency still have not reached the target and below standard of Central Java Province. This study aimed to describe factors associated with case finding of TB lungs patients based on characteristics, officer performance, and laboratory facilities of puskesmas. This research was a descriptive research with cross sectional approach. The samples was 21 TB program officers and 22 TB laboratory officers in all puskesmas in Dinas Kesehatan Kabupaten Batang. The samples were the total study population. Officers with an average age of 43.8 years were in the age group of the elderly (48.8%), most of officers were male (51.2%), highly educated (97.6%) were mostly D3 nurse (37,2%). The average of duration of P2TB officers 12 years and laboratory officer 11tahun. Training history less than 2 times (55,8%), officer knowledge level (46,5%). The performance of the suspect screening officer (47.6%), contact tracking (52.4%), counseling (47.6%), and performance of laboratory examination microscopic sputum officer (50%), condition of laboratory facilities (72.7% ) and availability of laboratory facilities (72.7%). Completeness of P2TB data recording (100%) and laboratory officers (59.1%).Suggestions that can be given areTB program officers and laboratory officer to improve performance in case finding of tuberculosis, training for those who have not attend training and increase knowledge.